2018
DOI: 10.17221/13/2018-pse
|View full text |Cite
|
Sign up to set email alerts
|

The biochar effect on soil respiration and nitrification

Abstract: ABSTRACTŠlapáková B., Jeřábková J., Voříšek K., Tejnecký V., Drábek O. (2018): The biochar effect on soil respiration and nitrification. Plant Soil Environ., 64: 114-119.Soil microorganisms play a main role in the nutrient cycle and they also play an important role in soil health. This article studies the influence of three rates of biochar (0.5, 1 and 3%) in comparison with control (0 biochar) in two different soils (Valečov and Čistá) on soil microbiota activities. The biochar was prepared from 80% of digest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In general, BC-chicken presented higher CO 2 emissions in the three soils under study, comparing with BC-cow and BC-pig. Similarly, Šlapáková et al [43] show not effect on soil respiration in soils amended with a BC of digestate from Zea mays (80%) and cellulose fibre (20%) in two soils incubated during 1-year. On the other hand, the higher levels of CO 2 emissions obtained from BC-chicken could be produced by the release of carbonates contained in the BC which could be higher in acidic soils according to Sheng and Zhu [44], who reported higher CO 2 emissions from an acidic Ferrasols (pH 5.19) rather than Phaeozems (pH 7.81).…”
Section: Ghg Emissionsmentioning
confidence: 85%
“…In general, BC-chicken presented higher CO 2 emissions in the three soils under study, comparing with BC-cow and BC-pig. Similarly, Šlapáková et al [43] show not effect on soil respiration in soils amended with a BC of digestate from Zea mays (80%) and cellulose fibre (20%) in two soils incubated during 1-year. On the other hand, the higher levels of CO 2 emissions obtained from BC-chicken could be produced by the release of carbonates contained in the BC which could be higher in acidic soils according to Sheng and Zhu [44], who reported higher CO 2 emissions from an acidic Ferrasols (pH 5.19) rather than Phaeozems (pH 7.81).…”
Section: Ghg Emissionsmentioning
confidence: 85%
“…Similarly, Paz-Ferreiro et al (2012) reported that soils amended with 4% biochar demonstrated lower respiration rate compared to 2% biochar and unamended control treatments. Typically, the addition of biochar into soils significantly increase respiration rate compared to untreated control, and the ideal respiration rate should be >0.7 mg CO2 g ˗1 dry soil (Wang et al, 2017;Moebius-Clune et al, 2017;Slapakova et al, 2018).…”
Section: Effects Of Sewage Sludge Derived Biochar Amendments On Soil ...mentioning
confidence: 99%